8.4-0.7t+2.2-1.4t=9-2.1t-6.4

Simple and best practice solution for 8.4-0.7t+2.2-1.4t=9-2.1t-6.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8.4-0.7t+2.2-1.4t=9-2.1t-6.4 equation:


Simplifying
8.4 + -0.7t + 2.2 + -1.4t = 9 + -2.1t + -6.4

Reorder the terms:
8.4 + 2.2 + -0.7t + -1.4t = 9 + -2.1t + -6.4

Combine like terms: 8.4 + 2.2 = 10.6
10.6 + -0.7t + -1.4t = 9 + -2.1t + -6.4

Combine like terms: -0.7t + -1.4t = -2.1t
10.6 + -2.1t = 9 + -2.1t + -6.4

Reorder the terms:
10.6 + -2.1t = 9 + -6.4 + -2.1t

Combine like terms: 9 + -6.4 = 2.6
10.6 + -2.1t = 2.6 + -2.1t

Add '2.1t' to each side of the equation.
10.6 + -2.1t + 2.1t = 2.6 + -2.1t + 2.1t

Combine like terms: -2.1t + 2.1t = 0.0
10.6 + 0.0 = 2.6 + -2.1t + 2.1t
10.6 = 2.6 + -2.1t + 2.1t

Combine like terms: -2.1t + 2.1t = 0.0
10.6 = 2.6 + 0.0
10.6 = 2.6

Solving
10.6 = 2.6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6(x-7)=12(x+4) | | f(2)+f(3)=f(5) | | -k+17=1 | | 6t^2+5t-4= | | 6x+2y=1356 | | (216x^6)^-2/3 | | 6a-12= | | 20+6r+8r-8=15r+18-r-6 | | 5(x-4)-5=2(x-10)+5+3x | | 4.7x=84.6 | | 6x-(2x-9)=45 | | 3x=14/3 | | 3+10c-11c=7 | | 14x+19x-8+2=-2x+2-8 | | 9y-6x=8 | | 7/9*9/14 | | 2(y-6)=y+3+2y | | -6(4x-6)+5(5x-6)-7=9-7 | | 8.2-3.5= | | (7b+3)(4b-3)=0 | | 6x-3x+x=-20 | | 3x-21+5x=-21 | | 3(4y-2)=-6+12y | | 3(q-15)=2q+10 | | 18m+24= | | -37-6x=14-3 | | x+0.03x=23.49 | | p(p-3)=0 | | 1/4(9x-20)= | | 5(a-2b)-3(a-2b)=0 | | 4=4x-4(3x+2) | | (8.2x-3.5)x=84.6 |

Equations solver categories